2021
DOI: 10.3390/jcm10214836
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Performance of Five Burnout Screening Tools: A Multicentre Study in Anaesthesiology, Intensive Care, and Ancillary Staff

Abstract: Burnout is an important occupational hazard and early detection is paramount in preventing negative sequelae in physicians, patients, and healthcare systems. Several screening tools have been developed to replace lengthy diagnostic tools for large-scale screening, however, comprehensive head–to–head evaluation for performance and accuracy are lacking. The primary objective of this study was to compare the diagnostic performance of five burnout screening tools, including a novel rapid burnout screening tool (RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
1
14
1
2
Order By: Relevance
“…Regarding diagnostic characteristics, such as sensitivity and specificity, past studies have found a wide range of sensitivity (approximately 50%–80%) and high specificity (approximately 80%–90%). 12 , 13 Our findings are similar to those of Knox et al, suggesting that the Japanese version has the same level of diagnostic performance as the original SMB. 12 However, the Knox et al study further pointed out that the SMB may estimate a lower prevalence of burnout than the MBI.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Regarding diagnostic characteristics, such as sensitivity and specificity, past studies have found a wide range of sensitivity (approximately 50%–80%) and high specificity (approximately 80%–90%). 12 , 13 Our findings are similar to those of Knox et al, suggesting that the Japanese version has the same level of diagnostic performance as the original SMB. 12 However, the Knox et al study further pointed out that the SMB may estimate a lower prevalence of burnout than the MBI.…”
Section: Discussionsupporting
confidence: 89%
“…There are other simple scales unrelated to the MBI, such as the Rapid Burnout Screening Tool (RBST), which is a free instrument developed by Ong et al 13 The RBST consists of four questions, one for each of the three dimensions of burnout and one for self‐assessment of burnout. The RBST has a higher diagnostic performance than the SMB 13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations